The Bible and Indigenous Theology - Caero Bustillos, Bernardeth (Concilium, 2022)
"I have come so that they may have life and have it abundantly" (John 10:10) Starting from the biblical quote "I have come so that they may have life and have it abundantly" (John 10:10), the subject of the Bible and Teología India / Teologías Amerindias (Indigenous Theology/Amerindian Theologies) will be addressed. In the history of colonialism on the American continent, the Bible played a preponderant role. That colonial period left theological and experiential wounds. Despite this, the indigenous peoples knew, throughout history, how to reread the meaning of the Bible in relation to their spiritualities and traditions. This rereading is reflected in the diversity of interpretations and perception of what is in the Bible.